Da'wah Efforts Against Social Deviance: The Impact of Religious Intensity on the Detachment of the Punk Community - Arif Rahman; Herman Herman (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
The purpose of this study is to determine the level of religious intensity of punk groups in West Java and their attachment and how the influence of punk religious intensity on the decline in their group attachment. This research uses a correlational approach that aims to detect the extent to which variations in a factor are related to variations in one or more other factors. After data processing, the results showed that 13% of punk children have a high intensity of religiosity, 43% are moderate and 44% are low. Regarding the level of attachment to the punk community, the results showed that 35% were categorized as high, 49% were moderate, and 16% were low. This means that 65% of punk children experience attachment to their community. This study shows that there is a strong correlation between religious intensity and disengagement in the punk community with a correlation coefficient of 0.745. This strong correlation implies a corrective effect of religion on the level of social deviance. This research also shows that the most effective da'wah to overcome social deviation is with the targhîb approach in the form of amar ma'ruf which is persuasive compared to the tarhîb approach in the form of nahyi munkar which tends to be repressive.